2012
DOI: 10.1007/s10578-012-0296-z
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition in Children with High Functioning Autism and Children with Social Phobia

Abstract: Recognizing facial affect is essential for effective social functioning. This study examines emotion recognition abilities in children aged 7-13 years with High Functioning Autism (HFA = 19), Social Phobia (SP = 17), or typical development (TD = 21). Findings indicate that all children identified certain emotions more quickly (e.g., happy < anger, disgust, sad < fear) and more accurately (happy) than other emotions (disgust). No evidence was found for negative interpretation biases in children with HFA or SP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 77 publications
2
43
0
1
Order By: Relevance
“…Of note, however, is a recent study of children with Social Phobia, High Functioning Autism and normal controls (ages 7-13 years), wherein no evidence was found for negative interpretation biases in children with SP or HFA who were similar to normal controls (Wong, Beidel, Sarver, & Sims, 2012). Children with HFA were less accurate in detecting mild affective expressions than controls.…”
Section: Cognitive Features and Perceptionmentioning
confidence: 89%
“…Of note, however, is a recent study of children with Social Phobia, High Functioning Autism and normal controls (ages 7-13 years), wherein no evidence was found for negative interpretation biases in children with SP or HFA who were similar to normal controls (Wong, Beidel, Sarver, & Sims, 2012). Children with HFA were less accurate in detecting mild affective expressions than controls.…”
Section: Cognitive Features and Perceptionmentioning
confidence: 89%
“…First, we hypothesized that social motivation would be positively correlated with performance on the FER task. As previous studies [6, 14, 15] have indicated specific stimuli that produce difficulty in FER, we hypothesized that this effect would be especially evident for low intensity emotions, adult faces, and anger. Second, we hypothesized that early-stage face perception, or N170 latency, would be negatively correlated with performance on the FER task (i.e.…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, these two processes may uniquely facilitate FER. Research indicates that deficits in FER are varied and may be affected by multiple components [1315]. Examination of these two hypotheses (perceptual/cognitive and motivational/affective) is crucial for clarifying the role of social motivation and perceptual aspects of FER in ASD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations